SYAIR HAJI DAN UMRAH JAMA’AH TAREKAT NAKSABANDIYAH DESA KEBUNDURIAN KECAMATAN GUNUNG SAHILAN KABUPATEN KAMPAR-RIAU - Amanan Amanan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
There are many kinds of tradition develop since the arrival of Islam in the village of Kebundurian, District of Gunung Sahilan, Kampar Regency, Riau province. One of them is a poem of tradition. Riau province becomes a center of Malay language and culture from the past up to now. The fact has produced the development of several kinds of poem, such as the poem related to other creatures. It can be seen how Malay people treat Terubuk fish kindly, or Nozam poem which tells about the death process dan the life of the world hereafter. Since the arrival of Tarekat in this area in 1938 from Godang island XIII Koto Kampar regency who was brought by Syekh Jakfar, this Tarekat bring several kinds of tradition, one of them is poem of Haji and Umrah. The poem tells about the story of Adam prophet and Eve who were parted for long time and met each other in Jabarrahma with joyful and they said Alhamdulillah to God who has blessed them.